Gen Z Empowerment Strategy in the Framework of Improving the Standard of Living in Indonesia Using SWOT Analysis - Nandi, Heigy; Ali, Rahma Saida; Andriyani; Suharnomo (Research Horizon, 2024)
Indonesia’s population is currently dominated by Generation Z, making up 27.94% of the total. However, with the economic recession of 2023, Generation Z has faced significant employment challenges, with 42.62% (or 4.3 million individuals) reported as unemployed in 2024, based on Sakernas data. Structural unemployment not only impacts economic growth and development but also poses mental health risks and threatens the productivity of an entire generation. This research aims to explore strategies for empowering Generation Z, leveraging their potential for innovation, creativity, and productivity. Using a qualitative, literature-based approach with SWOT analysis, this study examines both external (opportunities and threats) and internal (strengths and weaknesses) factors to develop alternative strategies. Key recommendations include certified entrepreneurship training through government and business collaboration, local material used to reduce costs, and digital marketing optimization. Additional strategies involve creating policies with stakeholders to support youth empowerment and leveraging government programs for talent and business capital. This research provides actionable insights to help unlock Generation Z's potential, improving their quality of life and contributing to sustainable national development.